Metode eksperimen untuk meningkatkan pembelajaran sains pada anak usia dini - Sriyono, Sriyono (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The purpose of this study was to determine the creativity of educators in improvingchildren's learning by means of experimental methods in improving science learning at an early age. This Classroom Action Research is to explore a group of knowledge and skills of early childhood education teachers in improving experimental methods through science learning. This study uses focus group discussions using open-ended questions to find out the data in the preliminary study or the problems that occur. This discussion discusses topics related to the science teaching teaching system that has been implemented so far. The results of the study show that learning science in the early childhood education curriculum is very important by applying the experimental method, namely learning and playing. The teacher as a facilitator by guiding students in carrying out experiments, namely volcanoes, paper flying boats and moving water up. This experimental method uses attractive, innovative and creative props to stimulate children to increase creativity through experiments.